Lezioni di Sistemi Dinamici - Ricci, Riccardo (Manuali - Scienze, 2016)
This work is based on the "Notes for the course of dynamic systems" written by Professor Riccardo Ricci in 2005 and subsequently reworked until the year of his death, which occurred in 2013. Starting from the latest version, the scholars have undertaken a review and expansion that led to this manual. The text is aimed at bachelor students of the courses in Mathematics, Physics and Engineering. Moreover, it presents the fundamental topics of Lagrangian mechanics and the dynamics of rigid bodies and variational principles, with a hint at Hamiltonian mechanics.